High-strength high-thermal-conductivity cast aluminum alloy with good thermal stability and preparation method thereof

By optimizing the Al-Si-Ni eutectic alloy system and processing technology, and adding Ni, Sr, and Sm elements, the problem of insufficient thermal stability of aluminum alloy conductors at high temperatures is solved, and the high thermal conductivity and mechanical properties are improved, satisfying the The performance requirements of high-voltage switches and other equipment are reduced.

CN119121005APending Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411121340.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing aluminum alloy conductors have insufficient thermal stability at high temperatures, resulting in a decrease in tensile strength, posing safety hazards, and are costly, making it difficult to meet the reliable operation needs of thermally conductive equipment such as high-voltage switches.

Method used

Using the Al-Si-Ni eutectic alloy system, through the alloy system optimization and treatment process, Ni, Sr and Sm elements were added, and the deterioration treatment and solid solution aging treatment were carried out to prepare high thermal conductivity, high mechanical properties and good thermal stability. Cast aluminum alloy.

Benefits of technology

The high thermal conductivity and excellent mechanical properties of cast aluminum alloy are achieved, which significantly improves its thermal stability, ensures the maintenance of tensile strength at high temperatures, meets the performance requirements of thermal conductivity equipment such as high voltage switches, and reduces the process cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004995181240000181
    Figure BDA0004995181240000181
  • Figure HDA0004995181250000011
    Figure HDA0004995181250000011
  • Figure HDA0004995181250000012
    Figure HDA0004995181250000012
Patent Text Reader

Abstract

The invention belongs to the technical field of high-thermal-conductivity and high-electrical-conductivity materials, and discloses a high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability and a preparation method thereof. The cast aluminum alloy is prepared from the following components in percentage by mass: 3 to 5.2 percent of Ni, 0.4 to 0.7 percent of Mg, 6.8 to 11 percent of Si, 0.04 to 0.15 percent of Sr, 0.1 to 0.35 percent of Sm and the balance of Al. The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is obtained by carrying out Sr and Sm modification treatment on a melt containing Al, Ni, Mg and Si and then carrying out casting and solid solution aging. The invention further discloses a preparation method of the cast aluminum alloy. The aluminum alloy is high in heat conductivity, excellent in mechanical property and better in aging resistance and high-temperature softening capacity, and a technical support is provided for development of aluminum alloy for typical heat-conducting and electric-conducting equipment of a high-voltage switch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aluminum alloy heat-conducting and electrical-conducting products, and in particular relates to a high-strength and high-thermal-conducting cast aluminum alloy with good thermal stability and a preparation method thereof. Background Art

[0002] Aluminum alloy has excellent thermal and electrical conductivity and can be used in the manufacture of key structural parts such as heat dissipation of electronic products, transmission wires, and power grid conduction. Taking high-voltage switch conductors as an example, copper has long been used for preparation, but it is expensive. "Replacing copper with aluminum" is the general trend, and aluminum alloy conductors have been used as switch components. A356 aluminum alloy has been successfully applied. After extrusion casting, it is heat treated to precipitate the dispersion strengthening phase, which can achieve the simultaneous improvement of conductivity and mechanical properties. In the peak aging state, the room temperature tensile strength of the alloy is as high as 250MPa, and the thermal conductivity is about 150W / (m·K). According to Ohm's law, the conductor parts will heat up during service, resulting in the continuation of the aging process, thus entering the over-aging state, resulting in the loss of room temperature strength. In addition, when the alloy is subjected to stress at high temperature, due to the softening of α-Al and the coarsening of the aging phase, the tensile strength required for failure may be much lower than the room temperature strength, causing safety hazards. In this context, it is urgent to develop high-strength and high-thermal conductivity cast aluminum alloys with good thermal stability to provide technical support for the reliable operation of high-voltage switches, which are typical thermal and electrical conductive devices.

[0003] The patent "A high thermal conductivity cast aluminum silicon alloy and its preparation method" (publication number: CN 110387490A) proposes a composition control and smelting process, adding 0.6% Cu to the Al-6Si-0.7Mg alloy. After heat treatment, the alloy has a tensile strength of up to 250MPa and a thermal conductivity of up to 160W / (m·K), but lacks thermal stability evaluation.

[0004] The present invention uses Al-Si-Ni eutectic alloy as the matrix material, and obtains a cast aluminum alloy with high thermal conductivity, excellent mechanical properties and high thermal stability through alloy system optimization and processing technology. The aluminum alloy of the present invention is used for high-voltage switches, which are typical thermal and electrical conductive devices, and promotes the development of aluminum alloys with high thermal conductivity and high thermal stability. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, an object of the present invention is to provide a high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability and a preparation method thereof.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability, mainly composed of the following components in percentage by mass:

[0008] Ni: 3-5.2%, preferably 4.8-5.2%;

[0009] Mg: 0.4-0.7%, preferably 0.5-0.7%;

[0010] Si: 6.8-11%, preferably 6.8-7.2%;

[0011] Sr: 0.04-0.15%, preferably 0.045-0.06%;

[0012] Sm: 0.1-0.35%, preferably 0.25-0.35%;

[0013] Al: margin.

[0014] The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is obtained by subjecting a melt containing Al, Ni, Mg, and Si to Sr and Sm modification treatment, followed by casting and solution aging.

[0015] The solution aging process refers to heat preservation at 525-535° C. for 2-5 hours, quenching, heat preservation at 195-205° C. for 1-15 hours (preferably 2-15 hours), and air cooling.

[0016] The quenching means that the sample is placed in water for 8 to 12 seconds within 1 to 5 seconds after being taken out.

[0017] The temperature of the modification treatment is 710-720° C. After Sr and Sm are added to the melt, they are stirred evenly and allowed to stand and keep warm for 15-30 minutes.

[0018] The method for preparing the high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability comprises the following steps:

[0019] 1) pure Al, Al-Si and Al-Ni master alloys are melted into a melt, Al-Mg master alloy is added, the melt is kept warm, stirred, cooled and allowed to stand; the melting temperature is 740-750° C., the heat preservation time is 15-30 min; the stirring time is 3-5 min, and the cooling refers to cooling to 710-720° C.;

[0020] 2) Adding Al-Sr and Al-Sm master alloys to the melt of step 1) for modification, stirring, and standing and keeping warm; the treatment temperature is 710-720° C., the stirring time is 5-10 minutes, and the standing and keeping warm time is 15-30 minutes;

[0021] 3) refining and deslagging the metamorphic melt, and casting the melt; the refining and deslagging treatment in step 3) specifically includes adding a refining agent and a deslagging agent, refining and deslagging, and standing and keeping warm; the standing and keeping warm time is 3 to 5 minutes; the temperature of the refining and deslagging treatment is 710 to 720° C.; cooling after casting; the cooling is air cooling, which means naturally cooling to room temperature in the air; wherein the casting method can be ordinary gravity casting or extrusion casting to obtain a cast aluminum alloy casting;

[0022] 4) Solution aging: The ingot obtained in step 3) is kept at 525-535°C for 2-5h, quenched, kept at 195-205°C for 1-15h (preferably 2-15h), and air-cooled. The quenching refers to transferring to water within 1-5s and soaking for 8-12s, and the water is room temperature water. The air cooling refers to natural cooling to room temperature in the air.

[0023] In step 1), the Al-Mg master alloy is Al-10Mg, and the Al-Ni master alloy is Al-10Ni master alloy.

[0024] In step 2), the Al-Sr master alloy is Al-10Sr, and the Al-Sm master alloy is Al-10Sm master alloy.

[0025] The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is used in the field of high-voltage switches, which are typical heat-conducting and electrical-conducting equipment, as a heat-conducting structural part.

[0026] Principle of the present invention:

[0027] Mg and Si: These elements have a high solid solubility in aluminum alloys. After solution aging, they can precipitate aging phases to achieve a better balance between strength and thermal conductivity.

[0028] Ni, Sr and Sm: These elements are almost not soluble in aluminum alloys and have little effect on the thermal conductivity of the alloy. During the actual solidification process, Ni reacts with Al to generate a large amount of Al3Ni heat-resistant phase, which improves the heat resistance of the alloy. At the same time, Ni can also be doped into β″ to further inhibit the growth of β″, which is beneficial to improving the alloy's resistance to aging softening, thereby ensuring that the tensile strength remains high under overheating conditions. Sr can refine the Si phase and spheroidize it to reduce the electron scattering rate and stress concentration effect, and simultaneously improve the conductivity and mechanical properties of the alloy. At the same time, it can also be doped into β″ to further inhibit the growth of β″ and improve thermal stability. Sm can refine the heat-resistant Al3Ni phase, improve the conductivity and mechanical properties of the alloy, especially enhance the dispersion strengthening effect of the Al3Ni phase at high temperatures, and significantly improve the high-temperature mechanical properties.

[0029] Thermal stability: The thermal stability of the alloy includes resistance to aging softening and resistance to high temperature softening. Aging softening refers to the phenomenon that the mechanical properties of the alloy are reduced due to the coarsening of the precipitate phase or other second phases during the long-term aging process; resistance to high temperature softening refers to the alloy's resistance to the weakening of the mechanical properties due to the coarsening of the second phase caused by high temperature. The high temperature in the present invention refers to 200°C.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] (1) The present invention achieves a good balance between strengthening and thermal conductivity, that is, higher strength and excellent thermal conductivity.

[0032] (2) The present invention makes full use of Ni and Sr to inhibit aging softening, and at the same time uses Sr and Sm to refine the eutectic structure, so that the thermal conductivity and mechanical properties of the alloy are significantly improved, and excellent thermal stability is exhibited.

[0033] (3) The process of the present invention is simple, and the metamorphic elements used are low-cost, so it is easy to achieve industrial mass production, and no harmful substances are discharged during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 and Figure 2 They are the optical microstructures in the as-cast state and the peak-aged state in Comparative Example 1 respectively;

[0035] Figure 3 and Figure 4 They are the optical microstructures in the as-cast state and the peak-aged state in Comparative Example 2 respectively;

[0036] Figure 5 and Figure 6 They are respectively the SEM image of the as-cast state in Comparative Example 2 and the EDS of the Mg2Si phase (black);

[0037] Figure 7 and Figure 8 They are respectively the optical microstructures in the as-cast state and the peak-aged state in Example 1;

[0038] Fig. 9 and Fig.10 They are respectively the optical microstructures in the as-cast state and the peak-aged state in Example 2;

[0039] Fig.11 and Fig.12 They are respectively the optical microstructures in the as-cast state and the peak-aged state in Example 3;

[0040] Fig.13 and Fig.14 They are respectively the optical microstructures in the as-cast state and the peak-aged state in Example 4;

[0041] Fig.15 and Fig.16 They are the optical microstructures in the as-cast state and the peak-aged state in Example 5, respectively. DETAILED DESCRIPTION

[0042] In order to more intuitively illustrate the implementation effect of the present invention, the preparation process of the high-strength and high-thermal-conductivity aluminum alloy of the present invention and its microstructure and performance characteristics are described in combination with the accompanying drawings, comparative examples and embodiments. In order to evaluate the anti-aging softening performance of the alloy, the room temperature strength loss value is defined as the difference in room temperature tensile strength between the alloy peak aging state and the long aging state.

[0043] Comparative Example 1: A356 aluminum alloy

[0044] The raw materials used in this comparative example are the commercial A356 alloy which is the most widely used in aluminum alloy extrusion casting production, and the mass percentage of its components are: Si: 6.5-7.5%, Fe<0.12%, Ca<0.12%, Sr: 0.010-0.018%, Mg: 0.3-0.4%, Mn<0.01%, Zn<0.1%, Ti<0.2%, and the balance is Al.

[0045] The alloy smelting, melt treatment process and heat treatment process parameters of this comparative example are as follows:

[0046] (1) Melting aluminum alloy and impurity sedimentation: The weighed A356 alloy was melted at 750°C, stirred for 3 minutes after melting, and allowed to stand and cool to 710-720°C;

[0047] (2) melt refining, deslagging and casting: the melt prepared in step (1) is subjected to refining and deslagging by adding a refining agent and a deslagging agent by nitrogen blowing process, the treatment temperature is 710-720° C., the melt is allowed to stand for 3 min, the melt is removed from the furnace and cast after deslagging, and a casting with a wall thickness of 12 mm is obtained. After air cooling, a sample is taken from the ingot for testing to obtain a cast A356 aluminum alloy;

[0048] (3) Aging: The ingot obtained in step (2) is kept in a resistance furnace at 525° C. for 3 h, then transferred to 25° C. clean water for quenching within 1 to 3 seconds, and then placed in a 200° C. blast furnace for 1 to 15 h. After air cooling, a sample is taken therefrom for testing to obtain an aged A356 aluminum alloy.

[0049] The microstructure and performance test methods of the alloy are as follows: The microstructure of the alloy is observed using an optical microscope (model: DMI3000-M, standard: JB / T7946-2017). The microstructure of the alloy is observed using a flash thermal conductivity meter (model: NETZSCHLFA-447, size: Thermal conductivity was measured using the electronic Brinell hardness tester (model: DHB-3000, standard: GB / T231.1-2018). The tensile curve was obtained using an electronic universal material testing machine (model: AG-X-100KN, standard: GB / T 228.1).

[0050] Thermal conductivity test:

[0051] The present invention strictly tests the thermal diffusion coefficient of aluminum alloy according to the test standard GB / T 22588-2008. The test instrument is a Netzsch LFA-457 laser thermal conductivity tester. The sample size is The upper and lower surfaces are polished with 600-grit sandpaper and the parallelism of the samples is ensured. Before the thermal diffusion coefficient test, graphite needs to be sprayed on the surface to increase the infrared emissivity and absorption ratio of the sample surface to light energy. The specific heat of the sample is calculated using the Neumann-Kopp criterion. The density test is carried out using the Archimedes drainage method and the DH-300 density balance according to the national standard GB / T 1423-19. The result of multiplying the above three physical quantities is the thermal conductivity of the alloy. The calculation formula is as follows:

[0052] λ=α·c p ·ρ

[0053] Where λ is the thermal conductivity of the material, W / (m·K); α is the thermal diffusivity of the material, mm 2 / s;c p is the specific heat of the material, J / (g·K); ρ is the density of the material, g / cm 3 .

[0054] Tensile properties test:

[0055] In order to evaluate the performance of the alloy in different states, the state of the alloy after air cooling to room temperature after casting is defined as the cast state. After aging treatment, the aging time t corresponding to the maximum hardness of the alloy is p is the peak aging time, and the long aging time is 15h.

[0056] The room temperature and high temperature (200°C) mechanical property test samples of the present invention are respectively processed into dumbbell shapes by wire cutting according to the national standards GB / T 228.1 and GB / T228.2, and then the mechanical properties are tested at a tensile rate of 1 mm / min. Three samples are tested and the average value is taken as the final test data. Before the test, the upper and lower surfaces and the sides are polished with 600-mesh sandpaper to eliminate the influence of defects on the experimental results. The room temperature and high temperature tensile property test instruments are Shimadzu universal testing machines, and the models are AG-X100KN and AG-Xplus 250kN, respectively.

[0057] Figure 1 and Figure 2 The as-cast and peak-aged optical microstructures of the A356 alloy in Comparative Example 1 are shown respectively. The as-cast structure is mainly composed of α-Al and coarse and long Si phases, which are mainly distributed near the α-Al grain boundary, which is not conducive to mechanical and thermal conductivity. After the peak aging treatment, the eutectic structure of the alloy is significantly passivated, and a large number of dispersed particles are precipitated in the matrix, which is conducive to the improvement of mechanical and thermal conductivity.

[0058] The cast hardness of A356 alloy is 54.2HBW, and the peak aging state thermal conductivity test result is 159.0W / (m·K). Continued aging will inevitably reduce the solid solution of the solute and further improve the thermal conductivity of the alloy, which obviously meets the current use requirements of high-voltage switches as typical thermal and electrical conductive equipment conductors. The room temperature tensile test results show that the peak aging state and long aging state tensile strength of the alloy are 258MPa and 152.9MPa respectively, and the room temperature strength loss value is 105.9MPa (40.7%), which does not meet the mechanical service requirements of high-voltage switches as typical thermal and electrical conductive equipment, and the alloy has weak resistance to aging softening. The high-temperature tensile properties of the long-aging state alloy were tested, and its high-temperature strength was 157.5MPa, which is relatively low. Overall, A356 aluminum alloy has low thermal stability.

[0059] Comparative Example 2: Al-11Si-5Ni-0.6Mg alloy

[0060] The raw materials used in Comparative Example 2 are industrial pure aluminum, Al-10Ni, Al-20Si and Al-10Mg, and the mass percentages of the components in the alloy are: Si: 11%, Ni: 5%, Mg: 0.6%, and the balance is Al. The smelting, melt treatment process and heat treatment process parameters are as follows:

[0061] (1) Molten aluminum alloy and impurity sedimentation:

[0062] According to the component ratio requirements, pure Al, Al-Si and Al-Ni master alloys are melted into a melt at 740-750°C, Al-Mg master alloy is added, kept warm for 25 minutes, stirred for 5 minutes, cooled and allowed to stand at 710-720°C.

[0063] (2) Melt refining, slag removal and casting: The melt prepared in step (1) is refined and slag removed by adding a refining agent and a slag remover by nitrogen blowing process at a treatment temperature of 710-720°C. The melt is allowed to stand for 5 min, and then the slag is removed from the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, samples are taken from the ingot for testing to obtain a cast alloy, i.e., a cast Al-11Si-5Ni-0.6Mg alloy.

[0064] (3) Aging treatment: The ingot obtained in step (2) was kept in a resistance furnace at 535°C for 3 h, then transferred to 25°C clean water within 2 to 5 seconds and immersed in it for 10 seconds, and then placed in a 200°C blast furnace and kept for 0 to 15 h. After air cooling, a sample was taken therefrom for testing to obtain an aged Al-11Si-5Ni-0.6Mg alloy.

[0065] Figure 3 and Figure 4 They are respectively the as-cast and peak-aged optical microstructures of the Al-11Si-5Ni-0.6Mg alloy of Comparative Example 2, Figure 5 and Figure 6 The following are the SEM images of the alloy in the cast state and the EDS of the Mg2Si phase (black). Its cast structure is mainly composed of α-Al, plate-shaped or long strip eutectic Si, long strip Al3Ni phase and granular Mg2Si phase, with a typical eutectic structure morphology. After solution treatment, the eutectic structure is significantly spheroidized, with spherical, rod-shaped and block-shaped alternating distribution, among which there is a relatively coarse Al3Ni phase.

[0066] But in general, the passivated structure reduces the tendency of stress concentration and increases the electron transmission channel, which is beneficial to the mechanical and conductive properties of the alloy.

[0067] The cast hardness of Al-11Si-5Ni-0.6Mg alloy is 104.3HBW, and the peak aging state thermal conductivity test result is 162.5W / (m·K). Continuing aging will inevitably reduce the solid solution of the solute and further improve the thermal conductivity of the alloy, which obviously meets the current use requirements of high-voltage switches as typical thermal and electrical conductive equipment conductors. The room temperature tensile test results show that the peak aging state and long aging state tensile strength of the alloy are 276.7MPa and 251.1MPa respectively, and the room temperature strength loss value is 25.6MPa, about 9.3%, which still meets the mechanical service requirements of high-voltage switches as typical thermal and electrical conductive equipment, and the alloy has good resistance to aging softening. The high-temperature tensile properties of the long-aging state alloy were tested, and its high-temperature strength was 194.1MPa, which is good. Overall, Al-11Si-5Ni-0.6Mg alloy has good thermal stability.

[0068] Compared with A356 alloy, the thermal conductivity of Al-11Si-5Ni-0.6Mg alloy in the peak aging state is 3.4W / (m·K) (2.2%) higher, the tensile strength in the long-aging state is 98.2MPa (64.2%) higher, and the strength loss value caused by long-aging is 79.5MPa (31.4%) lower, and the high-temperature strength is also 36.6MPa (23.2%) higher. Al-11Si-5Ni-0.6Mg alloy can have better thermal stability under the premise of thermal conductivity close to that of A356 aluminum alloy. To further illustrate the implementation effect of the present invention, the present invention is described in conjunction with the following embodiments.

[0069] Example 1: Al-11Si-5Ni-0.6Mg-0.1Sr alloy

[0070] The alloy system of this embodiment is modified by adding 0.1% Sr to the Al-11Si-5Ni-0.6Mg alloy of Comparative Example 1. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni and Al-10Sr. The percentage of each component in the alloy is: Si: 11%, Ni: 5%, Mg: 0.6%, Sr: 0.1%, and the balance is Al.

[0071] The smelting process of this embodiment is as follows:

[0072] (1) Molten aluminum alloy and impurity sedimentation:

[0073] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys are melted into a melt at 740-750°C, Al-Mg master alloy is added and kept warm for 30 minutes, stirred for 5 minutes, cooled and allowed to stand at 710-720°C;

[0074] (2) Alloy structure deterioration:

[0075] The aluminum alloy melt prepared in step (1) is scraped of the surface scum, and then Al-10Sr is added to the melt for modification, and after adding, the melt is stirred for 5 minutes until the alloy composition is uniform, and the temperature is kept at 710° C. for 15 minutes; wherein the weight percentage of the Sr element is 0.1% of the total weight of the alloy;

[0076] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process at a treatment temperature of 710-720° C. The melt was allowed to stand for 5 min, and then the melt was removed from the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-11Si-5Ni-0.6Mg-0.1Sr alloy.

[0077] (4) Aging treatment: The ingot obtained in step (3) is kept in a resistance furnace at 535°C for 5 h, then transferred to clean water at room temperature within 2 to 5 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 200°C forced air drying oven for 2 to 15 h. After air cooling, a sample is taken from the ingot for testing to obtain an aged Al-11Si-5Ni-0.6Mg-0.1Sr alloy.

[0078] The phase composition of the Al-11Si-5Ni-0.6Mg-0.1Sr alloy in this embodiment is consistent with that of the Al-11Si-5Ni-0.6Mg alloy in Comparative Example 1, but the morphology is different. The optical microstructures of the as-cast and peak-aged states are as follows: Figure 7 and Figure 8 As shown. In the cast state, compared with Comparative Example 1, the eutectic Si phase of the Al-11Si-5Ni-0.6Mg-0.1Sr alloy changes from plate-like or long strips to fine spherical dispersion, while Al3Ni changes from coarse long strips to rose petal distribution, which is more conducive to mechanical and conductive properties. After solution aging treatment, the eutectic Si phase is dispersed in the matrix as spherical fine particles, while the Al3Ni phase is distributed in the form of fishbone and large particles with passivated edges, and the alloy has a more obvious tendency of stress concentration.

[0079] After testing, the hardness of the cast alloy is 104.3HBW, and the thermal conductivity of the peak aged alloy is 168.3W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 311.9MPa and 275MPa respectively, and the room temperature strength loss value is 36.9MPa, about 11.8%, which is significantly higher than the room temperature tensile strength requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. The alloy has good resistance to aging softening. The high temperature tensile properties of the long aged alloy were tested, and its high temperature strength was 216.6MPa, which is good. Overall, the Al-11Si-5Ni-0.6Mg-0.1Sr alloy has good thermal stability.

[0080] Compared with Comparative Example 2, the hardness of this embodiment is similar, the peak aging state thermal conductivity and tensile strength are increased by 5.9W / (m·K) (3.6%) and 35.2MPa (12.7%), respectively, and the high temperature strength is increased by 22.5MPa (11.6%). This embodiment uses Sr to refine the Si phase and Al3Ni phase, thereby improving the mechanical and conductive properties at room temperature. Due to the refinement of the Al3Ni phase, the high temperature strength of the alloy is effectively improved.

[0081] Example 2: Al-9Si-4Ni-0.6Mg-0.15Sr alloy

[0082] The alloy system of this embodiment is based on the Al-11Si-5Ni-0.6Mg-0.1Sr alloy of Example 1, but 2% Si and 1% Ni are reduced, and 0.05% Sr is added for modification. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni and Al-10Sr. The percentage of each component in the alloy is: Si: 9%, Ni: 4%, Mg: 0.6%, Sr: 0.15%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0083] (1) Molten aluminum alloy and impurity sedimentation:

[0084] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys are melted into a melt at 740-750°C, Al-Mg master alloy is added, kept warm for 25 minutes, stirred for 4 minutes, cooled and allowed to stand at 710-720°C;

[0085] (2) Alloy structure deterioration:

[0086] The aluminum alloy melt prepared in step (1) is scraped to remove the scum on the surface, and then Al-10Sr is added to the melt for modification. After adding, the melt is stirred for 6 minutes until the alloy composition is uniform, and the melt is kept at 710° C. for 20 minutes; wherein the weight percentage of the Sr element is 0.15% of the total weight of the alloy;

[0087] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent using a nitrogen injection process. The treatment temperature was 710-720°C, and the melt was left to stand for 4 minutes. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-9Si-4Ni-0.6Mg-0.15Sr alloy.

[0088] (4) Aging treatment: The ingot obtained in step (3) was kept in a resistance furnace at 530° C. for 4 h, then transferred to clean water at room temperature within 2 to 5 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 205° C. forced air drying oven for 2 to 15 h. After air cooling, a sample was taken from the ingot for testing to obtain an aged Al-9Si-4Ni-0.6Mg-0.15Sr alloy.

[0089] After testing, the hardness of the cast alloy is 94.7HBW, and the thermal conductivity of the peak aged alloy is 173.4W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive device. The tensile strength of the alloy in the peak aged and long aged states are 243.4MPa and 202.5MPa respectively. The room temperature mechanical properties are relatively low, which makes it difficult to meet the service requirements of the high-voltage switch as a typical thermal and electrical conductive device. At high temperatures, the tensile strength of the alloy reaches 192.5MPa.

[0090] Compared with Example 1, the peak aging state thermal conductivity of this example is increased by 5.1W / (m·K) (3%), and it also has a similar high temperature tensile strength, but the room temperature mechanical properties are greatly reduced. Comparing the organization, it can be seen that the fishbone-shaped Al3Ni phase of this example is coarser, the stress concentration tendency is high, and the mechanical properties are reduced.

[0091] Fig. 9 and Fig.10 They are the optical microstructures in the as-cast state and the peak-aged state in Example 2 respectively.

[0092] Example 3: Al-9Si-4Ni-0.6Mg-0.1Sr alloy

[0093] The alloy system of this embodiment is based on the Al-9Si-4Ni-0.6Mg-0.15Sr alloy of Example 2, with 0.05% Sr reduced. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni and Al-10Sr. The percentage of each component in the alloy is: Si: 9%, Ni: 4%, Mg: 0.6%, Sr: 0.1%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing process and heat treatment process parameters of the alloy are as follows:

[0094] (1) Molten aluminum alloy and impurity sedimentation:

[0095] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added and kept warm for 25 minutes, stirred for 4 minutes, cooled and allowed to stand at 715°C;

[0096] (2) Alloy structure deterioration:

[0097] The aluminum alloy melt prepared in step (1) is scraped of the surface scum, and then Al-10Sr is added to the melt for modification, and after adding, the melt is stirred for 5 minutes until the alloy composition is uniform, and the temperature is kept at 710° C. for 15 minutes; wherein the weight percentage of the Sr element is 0.1% of the total weight of the alloy;

[0098] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process. The treatment temperature was 715° C. and the melt was allowed to stand for 4 min. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-9Si-4Ni-0.6Mg-0.1Sr alloy.

[0099] (4) Aging treatment: The ingot obtained in step (3) is kept in a resistance furnace at 530° C. for 4 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 195° C. forced air drying oven for 2 to 15 h. After air cooling, a sample is taken therefrom for testing to obtain an aged Al-9Si-4Ni-0.6Mg-0.1Sr alloy.

[0100] The phase composition of the Al-9Si-4Ni-0.6Mg-0.1Sr alloy in this embodiment is consistent with that of the Al-9Si-4Ni-0.6Mg-0.15Sr alloy in Example 2, but the morphology is different. The optical microstructures of the as-cast and peak-aged states are as follows: Fig.11 and Fig.12 As shown. In the cast state, compared with Example 2, the eutectic Si phase of the Al-9Si-4Ni-0.6Mg-0.1Sr alloy has a similar morphology and size, distributed in a spherical shape, while the Al3Ni phase changes from a coarse fishbone shape to an irregular block shape, distributed in an aggregated manner. After solution aging treatment, the alloy structure is significantly passivated, the Si phase is dispersed in the matrix in the form of fine spherical particles, and the Al3Ni phase is mainly distributed in the matrix in the form of large particles.

[0101] After testing, the hardness of the cast alloy is 97.1HBW, and the thermal conductivity of the peak aged alloy is 177.7W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive device. The tensile strength of the alloy in the peak aged and long aged states are 251.3MPa and 241.7MPa respectively, and the strength loss value at room temperature is 9.6MPa, about 3.8%. The alloy has good resistance to aging softening. At high temperature, the tensile strength of the alloy is 191.7MPa.

[0102] Compared with Example 2, the peak aging state thermal conductivity of this embodiment is increased by 4.3 W / (m·K) (2.5%), the room temperature mechanical properties are effectively improved, and it also has a similar high temperature tensile strength.

[0103] Compared with Comparative Example 2, the peak aging state thermal conductivity of this embodiment is increased by 15.3W / (m·K) (9.4%), but the peak aging and long aging state tensile strengths are reduced by 25.4MPa and 9.4MPa respectively, and the mechanical properties are poor. The Sr content of this embodiment is too high, which promotes the coarsening of the Al3Ni phase, thereby significantly reducing the mechanical properties.

[0104] Example 4: Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy

[0105] The alloy system of this embodiment is based on the Al-9Si-4Ni-0.6Mg-0.1Sr alloy of Example 3, with 1% Si and 1% Ni reduced and 0.1% Sm added. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni, Al-10Sr and Al-10Sm. The percentage of each component in the alloy is: Si: 8%, Ni: 3%, Mg: 0.6%, Sr: 0.1%, Sm: 0.1%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0106] (1) Molten aluminum alloy and impurity sedimentation:

[0107] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added and kept warm for 20 minutes, stirred for 4 minutes, cooled and allowed to stand at 720°C;

[0108] (2) Alloy structure deterioration:

[0109] The aluminum alloy melt prepared in step (1) is scraped to remove the scum on the surface, and then Al-10Sr and Al-10Sm are added to the melt for modification, and stirred for 7 minutes after addition until the alloy composition is uniform, and kept at 715° C. for 20 minutes; wherein the weight percentages of Sr and Sm elements are 0.1% and 0.1% of the total weight of the alloy respectively;

[0110] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process. The treatment temperature was 720° C. and the melt was allowed to stand for 4 min. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy.

[0111] (4) Aging treatment: The ingot obtained in step (3) is kept in a resistance furnace at 535°C for 4 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 200°C forced air drying oven for 2 to 15 h. After air cooling, a sample is taken from it for testing to obtain an aged Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy.

[0112] The phase composition of the Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy in this embodiment is consistent with that of the Al-9Si-4Ni-0.6Mg-0.1Sr alloy in Example 3, but the morphology is different. The optical microstructures of the as-cast and peak-aged states are as follows: Fig.13 and Fig.14 As shown. In the cast state, compared with Example 3, the Si phase size of the Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy is greatly reduced, and the Al3Ni phase is also greatly refined, presenting long strips and particles. After solution treatment, the structure is greatly spheroidized, with a large number of spherical Si phases and Al3Ni phases dispersed in the matrix, and a small amount of Al3Ni phases in rod form.

[0113] After testing, the hardness of the cast alloy is 101.71HBW, and the thermal conductivity of the peak aged alloy is 179.9W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 304.6MPa and 245.9MPa respectively, and the room temperature strength loss value is 58.7MPa, about 19.3%. The alloy has excellent resistance to aging softening, and the long aged tensile strength is close to the service requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. Its high temperature tensile strength is as high as 205.8MPa, and the alloy has excellent thermal stability.

[0114] Compared with Example 3, the peak aging state thermal conductivity of this embodiment is increased by 2.2W / (m·K) (1.2%), the peak aging state tensile strength is increased by 53.3MPa (21.2%), the long aging state tensile strength is increased by 4.2MPa (1.7%), and the high temperature strength is increased by 14.1MPa (7.4%). Comparing the organization, it can be seen that the Si phase and Al3Ni phase of this embodiment are finer, the probability of electron transmission scattering is effectively reduced, and the dispersion strengthening effect is significant, so the mechanical and conductive properties of the alloy are significantly improved.

[0115] Example 5: Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy

[0116] The alloy system of this embodiment is based on the Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy of Example 4, with 0.05% Sr reduced and 0.2% Sm increased. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni, Al-10Sr and Al-10Sm. The percentage of each component in the alloy is: Si: 8%, Ni: 3%, Mg: 0.6%, Sr: 0.05%, Sm: 0.3%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0117] (1) Molten aluminum alloy and impurity sedimentation:

[0118] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added and kept warm for 20 minutes, stirred for 4 minutes, cooled and allowed to stand at 720°C;

[0119] (2) Alloy structure deterioration:

[0120] The aluminum alloy melt prepared in step (1) is scraped to remove the scum on the surface, and then Al-10Sr and Al-10Sm are added to the melt for modification, and after adding, the melt is stirred for 10 minutes until the alloy composition is uniform, and the melt is kept at 720° C. for 30 minutes; wherein the weight percentages of Sr and Sm elements are 0.05% and 0.3% of the total weight of the alloy, respectively;

[0121] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process. The treatment temperature was 720° C. and the melt was allowed to stand for 4 min. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy.

[0122] (4) Aging treatment: The ingot obtained in step (3) was kept in a resistance furnace at 535°C for 4 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 195°C forced air drying oven for 2 to 15 h. After air cooling, a sample was taken from the ingot for testing to obtain an aged Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy.

[0123] The phase composition of the Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy in this embodiment is consistent with that of the Al-8Si-3Ni-0.6Mg-0.1Sr-0.1Sm alloy in Example 4, but the morphology is different. The optical microstructures of the as-cast and peak-aged states are as follows: Fig.15 and Fig.16 As shown. In the cast state, compared with Example 4, the Si phase size and morphology of the Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy are similar, while the Al3Ni phase is further refined and distributed in fine particles. After solution aging treatment, its structure is completely spherical and dispersed in the matrix.

[0124] After testing, the hardness of the cast alloy is 97.5HBW, and the thermal conductivity of the peak aged alloy is 182.8W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 325.1MPa and 247.8MPa respectively, and the room temperature strength loss value is 77.3MPa, about 23.8%. The alloy has good resistance to aging softening, and the long aged tensile strength is close to the service requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. Its high temperature tensile strength is as high as 211.8MPa, and the alloy has excellent thermal stability.

[0125] Compared with Example 4, the peak aging state thermal conductivity of this embodiment is increased by 2.9W / (m·K) (1.6%), the peak aging state tensile strength is increased by 20.5MPa (6.7%), the long aging state tensile strength is close, and the high temperature strength is increased by 6MPa (2.9%). Comparing the organization, it can be seen that the Al3Ni phase of this embodiment is finer, and the dispersion strengthening effect of the electron transmission channel and the heat-resistant Al3Ni phase are effectively increased, so the mechanical and conductive properties of the alloy are significantly improved, but the reduction of Sr content makes the alloy's resistance to aging softening relatively weakened, so the room temperature strength loss value is increased by 18.6MPa (31.7%).

[0126] Example 6: Al-7Si-4Ni-0.6Mg-0.05Sr-0.2Sm alloy

[0127] The alloy system of this embodiment is based on the Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy of Example 5, with 1% Si, 1% Ni and 0.1% Sm reduced. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni, Al-10Sr and Al-10Sm. The percentage of each component in the alloy is: Si: 7%, Ni: 4%, Mg: 0.6%, Sr: 0.05%, Sm: 0.2%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0128] (1) Molten aluminum alloy and impurity sedimentation:

[0129] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added, kept warm for 15 minutes, stirred for 3 minutes, cooled and allowed to stand at 720°C;

[0130] (2) Alloy structure deterioration:

[0131] The aluminum alloy melt prepared in step (1) is scraped of the surface scum, and then Al-10Sr and Al-10Sm are added to the melt for modification, and stirred for 8 minutes after addition until the alloy composition is uniform, and kept at 715° C. for 25 minutes; wherein the weight percentages of Sr and Sm elements are 0.05% and 0.2% of the total weight of the alloy, respectively;

[0132] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent using a nitrogen injection process. The treatment temperature was 720°C, and the melt was left to stand for 4 minutes. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-7Si-4Ni-0.6Mg-0.05Sr-0.2Sm alloy.

[0133] (4) Aging treatment: The ingot obtained in step (3) was kept in a resistance furnace at 535°C for 4 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 195°C forced air drying oven for 2 to 15 h. After air cooling, a sample was taken from the ingot for testing to obtain an aged Al-7Si-4Ni-0.6Mg-0.05Sr-0.2Sm alloy.

[0134] The alloy system, basic components and preparation process in this embodiment are similar to those in Example 5, so its organizational characteristics are also similar to those of the Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy, but the size of the Al3Ni phase is slightly increased.

[0135] After testing, the hardness of the cast alloy is 100.4HBW, and the thermal conductivity of the peak aged alloy is 183.5W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 310.8MPa and 249.6MPa respectively, and the room temperature strength loss value is 61.2MPa, about 19.7%. The alloy has good resistance to aging softening, and the long aged tensile strength is close to the service requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. Its high temperature tensile strength is as high as 210.9MPa, and the alloy has excellent thermal stability.

[0136] Compared with Example 5, the peak aging state thermal conductivity of this embodiment is increased by 0.7W / (m·K) (0.4%), the peak aging state tensile strength is reduced by 14.3MPa (4.4%), the long-aging state room temperature and high temperature tensile strength are close, and the room temperature strength loss value is reduced by 16.1MPa (20.8%). The increase of Ni effectively improves the alloy's resistance to aging softening, but by comparing the organization, it can be seen that the Al3Ni phase of this embodiment is slightly coarsened, offsetting the effect of the improvement of thermal conductivity caused by the lack of some Si; at the same time, the dispersion strengthening effect of a single Al3Ni phase is slightly reduced, but the overall increase in quantity makes up for the reduction, and the thermal stability of the alloy is effectively improved.

[0137] Example 7: Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy

[0138] The alloy system of this embodiment is based on the Al-7Si-4Ni-0.6Mg-0.05Sr-0.2Sm alloy of Example 6, with 1% Ni and 0.1% Sm reduced. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni, Al-10Sr and Al-10Sm. The percentage of each component in the alloy is: Si: 7%, Ni: 5%, Mg: 0.6%, Sr: 0.05%, Sm: 0.3%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0139] (1) Molten aluminum alloy and impurity sedimentation:

[0140] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added, kept warm for 15 minutes, stirred for 3 minutes, cooled and allowed to stand at 720°C;

[0141] (2) Alloy structure deterioration:

[0142] The aluminum alloy melt prepared in step (1) was scraped to remove the scum on the surface, and then Al-10Sr and Al-10Sm were added to the melt for modification, and after adding, the melt was stirred for 10 minutes until the alloy composition was uniform, and then kept at 720° C. for 30 minutes;

[0143] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process. The treatment temperature was 720° C. and the melt was allowed to stand for 4 min. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy.

[0144] (4) Aging treatment: The ingot obtained in step (3) was kept in a resistance furnace at 535°C for 4 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 195°C forced air drying oven for 2 to 15 h. After air cooling, a sample was taken from the ingot for testing to obtain an aged Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy.

[0145] The basic components of the alloy system in this embodiment and its preparation process are similar to those of the Al-8Si-3Ni-0.6Mg-0.05Sr-0.3Sm alloy in Example 5, so its organizational characteristics are also similar. After solution aging, a fully globalized eutectic structure is obtained, which has more spherical Al3Ni phases than Example 5.

[0146] After testing, the hardness of the cast alloy is 102.2HBW, and the thermal conductivity of the peak aged alloy is 185.1W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 315.7MPa and 257.7MPa respectively, and the room temperature strength loss value is 58MPa, about 18.4%. The alloy has good resistance to aging softening, and the long aged tensile strength is close to the service requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. Its high temperature tensile strength is as high as 216.3MPa, and the alloy has excellent thermal stability.

[0147] Compared with Example 6, the peak aging state thermal conductivity of this embodiment is increased by 1.6W / (m·K) (0.9%), the peak aging state and long aging state tensile strength at room temperature are increased by 4.9MPa (1.6%) and 8.1MPa (3.2%), respectively, and the room temperature strength loss value is reduced by 3.2MPa (5.2%). At high temperatures, the tensile strength of the alloy is increased by 5.4MPa (2.6%). By comparing the components, it can be seen that the increase in Ni effectively improves the alloy's resistance to aging softening, while the increase in Sm effectively improves the metamorphic effect, the increase in the number of spherical Al3Ni particles, and the enhancement of the dispersion strengthening effect effectively improve the high-temperature mechanical properties of the alloy, which greatly increases the mechanical properties and thermal stability. In addition, the more effective refinement of Al3Ni improves the electron transmission channel, so the thermal conductivity of the alloy is effectively improved.

[0148] Example 8: Al-7Si-5Ni-0.4Mg-0.05Sr-0.3Sm alloy

[0149] The alloy system of this embodiment is based on the Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy of Example 7, with 0.2% Mg reduced. The raw materials used to prepare the alloy include: industrial pure aluminum, Al-20Si, Al-10Mg, Al-10Ni, Al-10Sr and Al-10Sm. The percentage of each component in the alloy is: Si: 7%, Ni: 5%, Mg: 0.4%, Sr: 0.05%, Sm: 0.3%, and the balance is Al. The smelting process of this embodiment is similar to that of Example 1, except that the processing parameters are slightly different. The smelting, melt processing and heat treatment process parameters of the alloy are as follows:

[0150] (1) Molten aluminum alloy and impurity sedimentation:

[0151] According to the composition ratio requirements, pure Al, Al-Si and Al-Ni master alloys were melted into a melt at 740-750°C, Al-Mg master alloy was added, kept warm for 15 minutes, stirred for 3 minutes, cooled and allowed to stand at 720°C;

[0152] (2) Alloy structure deterioration:

[0153] The aluminum alloy melt prepared in step (1) was scraped to remove the scum on the surface, and then Al-10Sr and Al-10Sm were added to the melt for modification, and after adding, the melt was stirred for 10 minutes until the alloy composition was uniform, and then kept at 720° C. for 30 minutes;

[0154] (3) Melt refining, slag removal and casting: The melt prepared in step (2) was refined and slag removed by adding a refining agent and a slag removal agent by nitrogen blowing process. The treatment temperature was 720° C. and the melt was allowed to stand for 3 min. After slag removal, the melt was taken out of the furnace for casting to obtain a casting with a wall thickness of 12 mm. After air cooling, a sample was taken from the ingot for testing to obtain a cast Al-7Si-5Ni-0.4Mg-0.05Sr-0.3Sm alloy.

[0155] (4) Aging treatment: The ingot obtained in step (3) is kept in a resistance furnace at 525°C for 3 h, then transferred to clean water at room temperature within 1 to 3 seconds and immersed in it for 10 seconds (solution treatment), and then placed in a 195°C forced air drying oven for 2 to 15 h. After air cooling, a sample is taken from the ingot for testing to obtain an aged Al-7Si-5Ni-0.4Mg-0.05Sr-0.3Sm alloy.

[0156] The basic components of the alloy system in this embodiment and its preparation process are similar to those of the Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy in Example 7, so its organizational characteristics are also similar.

[0157] After testing, the hardness of the cast alloy is 95.1HBW, and the thermal conductivity of the peak aged alloy is 192.7W / (m·K), which is significantly higher than the performance requirements of the existing high-voltage switch as a typical thermal and electrical conductive equipment. The peak aged and long aged tensile strengths of the alloy are 282.5MPa and 241.1MPa respectively, and the room temperature strength loss value is 41.4MPa, about 14.7%. The alloy has good resistance to aging softening, but the long aged tensile strength is lower than the service requirements of the high-voltage switch as a typical thermal and electrical conductive equipment. Its high temperature tensile strength is as high as 207.2MPa, which is still a relatively high value.

[0158] Compared with Example 7, the peak aging state thermal conductivity of this embodiment is increased by 7.6W / (m·K) (4.1%), the peak aging state and long aging state tensile strength at room temperature are reduced by 33.2MPa (10.5%) and 16.6MPa (6.4%), respectively, and the room temperature strength loss value is reduced by 16.6MPa (6.4%). At high temperatures, the tensile strength of the alloy is reduced by 9.1MPa (4.2%). By comparing the components, it can be seen that the reduction of Mg reduces the aging strengthening effect and high temperature strength of the alloy, while the thermal conductivity is correspondingly improved. Overall, the thermal stability of the alloy does not change much, the conductivity is excellent, but the mechanical properties are insufficient.

[0159] In order to intuitively compare the beneficial effects of the present invention, the hardness, thermal conductivity and tensile strength of the alloys in the comparative examples and embodiments are summarized in Table 1.

[0160] Table 1 Properties of various alloys in comparative examples and embodiments

[0161]

[0162] When aluminum alloy is used as a conductor for high-voltage switches, which are typical heat-conducting and electrical-conducting devices, it not only requires good thermal stability and high strength, but also high thermal conductivity. The electrical conductivity of metal conductors is positively correlated with the thermal conductivity of the conductors. The higher the electrical conductivity, the stronger the thermal conductivity of the conductor.

[0163] The alloy of the present invention has good thermal stability and high strength and high thermal conductivity. The Al-7Si-5Ni-0.6Mg-0.05Sr-0.3Sm alloy of Example 7 has the best comprehensive performance. After long-aging treatment, compared with the long-aged A356 alloy of Comparative Example 1, the thermal conductivity of the cast aluminum alloy (16.4%), the peak aging state tensile strength (22.4%) and the long-aging state tensile strength (68.5%) are improved simultaneously. In particular, the long-aging state strength is reduced by 47.1 MPa (44.8%) relative to the strength value lost in the peak aging state, which can meet the performance requirements of the current high-strength and high-thermal conductivity aluminum alloy materials for resistance to 200°C aging softening in the field of high-voltage switches as typical conductors.

[0164] The implementation methods of the present invention are not limited to the embodiments described, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability, characterized in that: Mainly composed of the following components by mass percentage composition: Ni: 3-5.2% Mg: 0.4~0.7% Si: 6.8~11% Sr:0.04~0.15% Sm: 0.1~0.35% Al: margin; The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is obtained by subjecting a melt containing Al, Ni, Mg, and Si to Sr and Sm modification treatment, followed by casting and solution aging.

2. The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 1, characterized in that: Mainly composed of the following components by mass percentage composition: Ni: 4.8~5.2% Mg: 0.5~0.7% Si: 6.8~7.2% Sr:0.045~0.06% Sm: 0.25~0.35% Al: margin.

3. The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 1, characterized in that: The solution aging process refers to heat preservation at 525-535°C for 2-5 hours, quenching, heat preservation at 195-205°C for 1-15 hours, and air cooling; The temperature of the modification treatment is 710-720°C; After Sr and Sm are added to the melt, stir evenly and let it stand and keep warm for 15 to 30 minutes.

4. The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 3, characterized in that: In the solution aging, the temperature is kept at 195-205°C for 2-15 hours; The quenching means that the sample is placed in water for 8 to 12 seconds within 1 to 5 seconds after being taken out.

5. The method for preparing a high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) pure Al, Al-Si and Al-Ni master alloys are melted into a melt, Al-Mg master alloy is added, the melt is kept warm, stirred, cooled and allowed to stand; 2) adding Al-Sr and Al-Sm master alloys to the melt of step 1) for modification, stirring, and standing to keep warm; 3) Refining and removing slag from the deteriorated melt and casting it into a mold; 4) Solution aging: The ingot obtained in step 3) is kept at 525-535° C. for 2-5 h, quenched, kept at 195-205° C. for 1-15 h, and air-cooled.

6. The method for preparing the high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 5, characterized in that: In step 1), the melting temperature is 740-750°C, the insulation time is 15-30 min, the stirring time is 3-5 min, and the cooling refers to cooling to 710-720°C; In step 2), the treatment temperature is 710-720°C, the stirring time is 5-10 minutes, and the standing and heat preservation time is 15-30 minutes; In step 4), the heat treatment is carried out at 195-205°C for 2-15 hours, followed by air cooling; the quenching refers to transferring to water within 1-5 seconds and soaking for 8-12 seconds, wherein the water is room temperature water; and the air cooling refers to natural cooling to room temperature in the air.

7. The method for preparing the high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 5, characterized in that: In step 3), the refining and slag removal treatment specifically comprises adding a refining agent and a slag removal agent, refining and slag removal, standing and heat preservation; cooling after casting; In step 1), the Al-Mg master alloy is Al-10Mg, and the Al-Ni master alloy is Al-10Ni master alloy; In step 2), the Al-Sr master alloy is Al-10Sr, and the Al-Sm master alloy is Al-10Sm master alloy.

8. The method for preparing the high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to claim 7, characterized in that: In step 3) three-dimensional refining and slag removal, the standing and heat preservation time is 3 to 5 minutes; the refining and slag removal temperature is 710 to 720° C.; the cooling is air cooling, which means natural cooling to room temperature in the air.

9. The use of the high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability according to any one of claims 1 to 4, characterized in that: The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is used in the field of thermally conductive and electrically conductive equipment as a thermally conductive structural part.

10. The use according to claim 9, characterized in that: The high-strength and high-thermal-conductivity cast aluminum alloy with good thermal stability is used in the field of high-voltage switches as a thermally conductive structural member.